The Church and Poverty in Indonesia: A Theological Analysis Based on the Thought of Gustavo Gutiérrez - Ligawan, Andry (SAINT PAUL'S REVIEW, 2025)
Poverty is a complex and ongoing issue that impacts various aspects of people's lives around the world, including in Indonesia. This article explores the challenges faced by Indonesian society in terms of poverty, despite a decline in the number of poor people in recent years. Liberation theology introduced by Gustavo Gutiérrez is highly relevant in this context, emphasizing the need for social action oriented towards justice and solidarity. Gutiérrez argues that the church should function as a place of worship and as an active agent of change in fighting for the rights of disadvantaged communities. Through education and empowerment programs, churches are expected to help people understand their situation and empower them to fight for their rights. Gutiérrez also highlighted that believers can achieve spiritual experiences by caring for others, especially those living in poverty. By creating communities based on love, justice, and solidarity, the church has the potential to significantly impact society. The church's concrete advocacy and social engagement actions reflect its commitment to justice and liberation. Therefore, the church can actively build a better world where everyone, especially marginalized ones, can experience God's love and justice daily.